ANALYSIS OF MIX DESIGN BETON HOW DOE (ENGLISH) AND ACI (AMERICA) - Agus Santoso (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2002)
This research was aimed to describe concrete mix design using British DOE and American AC/ methods viewedfrom concrete compressive strength and cost per-m', The mix design research used materials of sand and split from Krasak River, Nusantara brand Portland cement, and ground water from Faculty of Engineering UNY They were 10 samples each methods of (J 5 x15 x 15) em dimension. The data were collected by meant of experiment in the Laboratory of Building Materials, Faculty of Engineering, UNY, and analyzed descriptively. The results were that, to design concrete with K.225 characteristic, the DOE method required mix composition of PC : sand: split = I : 1,58: 3,49 with slump = 13 em, the average weight of concrete cubes = 8,066 kgs and characteristic of compressive strength = 263,1 kg/em